2017
DOI: 10.1080/0907676x.2017.1330894
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing translation revision competence: a pilot study on the ‘fairness and tolerance’ attitudinal component

Abstract: Although translation revision plays a crucial role in the production of highquality translations, research into translation revision competence (TRC) is relatively new and underdeveloped compared with research into translation competence (TC). This article addresses that gap by focusing on the validation of the TRC model developed by Robert, Remael and Ureel. Using questionnaires and revision tasks in a pretest-posttest experimental design, we investigated whether a course on revision and editing affected the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
7
0
4
Order By: Relevance
“…The first validation pilot studies of the TRC model (Rigouts Terryn et al 2017;Robert et al 2017b;Robert et al 2018) showed that revision trainees used the same search tools as translation trainees (with no revision training), but did so more frequently. Revision trainees also conducted more searches to justify their changes, and their searches were more rigorous.…”
Section: Robert Et Al's (2017a) Model Of Translation Revision Competencementioning
confidence: 99%
See 1 more Smart Citation
“…The first validation pilot studies of the TRC model (Rigouts Terryn et al 2017;Robert et al 2017b;Robert et al 2018) showed that revision trainees used the same search tools as translation trainees (with no revision training), but did so more frequently. Revision trainees also conducted more searches to justify their changes, and their searches were more rigorous.…”
Section: Robert Et Al's (2017a) Model Of Translation Revision Competencementioning
confidence: 99%
“…First, to ensure that the 'tools' as a potential covariate remained constant for the three tasks. Second, research has shown that translation trainees and revision trainees use the same tools but slightly differently (e.g., Robert et al 2017b). Third, we decided not to allow any internet use; otherwise, students would have translated using DeepL or Google Translate and their translations would no longer have been translations 'proper', that is, starting from scratch.…”
Section: Robert Et Al's (2017a) Model Of Translation Revision Competencementioning
confidence: 99%
“…The revision and post-editing teaching as well as the acquisition of skills and competences are always among hot topics in the field (O'Brien, 2002, Robert et al, 2017, 2018, Scocchera, 2019, Nitzke et al, 2019. The last part, chapters 10 to 12, focuses on This volume presents the latest research on translation revision and post-editing in various contexts, including government department, translation agencies, literary publishing sector, volunteer sector, etc.…”
mentioning
confidence: 99%
“…Sobre la base de las propuestas de evaluación del producto, utilizadas en las investigaciones que mencionamos en los párrafos anteriores, y de las recomendaciones de Hansen (2013b), diseñamos un instructivo para las evaluadoras externas (ver Tabla 13), que funcionara como encargo de revisión (Künzli, 2007;Parra Galiano, 2016;Robert, I. et al, 2017;Robert, I. et al, 2018 Albir, 1996Albir, , 2011Hansen, 2009a;Mossop, 2014;Tolosa Igualada, 2013: 158-160) y es muy similar a la que habitualmente emplean las evaluadoras en sus tareas docentes (ver secciones 3.4.2 y 3.3.5.4).…”
Section: La Evaluación De La Traducción Con Fines Investigativosunclassified
“…Las categorías de este segundo nivel de evaluación nos permiten, por un lado, establecer un segundo nivel de tolerancia en las evaluaciones, ya que es comprensible que haya errores, en especial, porque se trata de traducciones hechas por traductores en formación. Por otro lado, esta clasificación permite controlar, en cierta medida, los niveles de subjetividad de cada evaluadora, a lo que refieren Hagemann (2020), Robert et al (2017) y Robert et al (2018) (ver sección 2.3.4).…”
Section: Datos Que Surgen Del Análisis Del Productounclassified